The Anomaly of Law Enforcement Against the Spread of Fake News in Indonesia - Ismed, Mohamad (Journal Evidence Of Law, 2025)
Abstract The spread of fake news or hoaxes in Indonesia has become an increasingly pressing social issue, impacting both social and political stability. Although the Electronic Information and Transactions Law (UU ITE) provides a legal basis for addressing this issue, its implementation faces significant challenges. This study aims to analyze the anomalies in law enforcement against the spread of hoaxes in Indonesia, focusing on the misalignment between regulations, law enforcement practices, and their impact on freedom of expression. The research employs a normative legal approach using three primary approaches: legislative, conceptual, and case-based. The findings indicate that while the UU ITE provides clear legal grounds, there is ambiguity in the definition of hoaxes, which may lead to misuse of the law. The study also reveals that law enforcement against hoaxes is often influenced by political factors, affecting fairness and transparency in the legal process. Therefore, reform in both regulations and law enforcement practices is necessary to establish a more just and effective legal system.